The Comparison of a Roundabout Traffic Delay Estimation between SUMO and IHCM 1997 on Roundabout - Tina Andriyana (Journal of the Civil Engineering Forum, 2013)
Transportation is an important sector to support the development of countries in terms of highway design, road systems and traffic management. As users of transport infrastructure, human has close relationship to the field of transportation. Their driving behavior affects vehicle movements and may cause conflicts. In order to investigate the conflicts such as traffic delay, there are two different calculation methods using SUMO software and IHCM 1997 manually. The objective of this research is to compare the calculation methods of traffic delay using IHCM 1997 and SUMO which more appropriately with the actual condition.The research location is in Idröttsparken roundabout, Norrköping, Sweden which has four arms. The data collection is conducted during three days in the morning and afternoon. Types of data collection in this research were traffic flow and its turning, travel time and queue length. The queue length data is converted into traffic delay data for observation data. In SUMO, the traffic delay value is the mean halting duration. In IHCM 1997, the calculation of traffic delay needs several data i.e. roundabout geometric, capacity, and degree of saturation. To analyze data, the statistical method is used i.e. normality test, parametric and non-parametric test and also linear regression method.The result showed the traffic delay in observation data is higher than delay in SUMO result and IHCM 1997 calculation. The statistical results showed that the traffic delay of SUMO, and IHCM 1997 have no similarities to the observation. Furthermore, from the linear regression result, only SUMO result has the highest value for determination coefficient (R2) compared to IHCM 1997 as shown in the West and South arms for SUMO result in the morning measurement. It means SUMO more representatives the observation compared to IHCM 1997. It is occurred because SUMO is developed in Europe and also the location for this research is in Sweden, Europe which has very different traffic condition from Indonesia.Keywords: Roundabout, traffic delay, SUMO, IHCM 1997.